Holocene environmental history of Lake Vuolep Njakajaure (Abisko National Park, Northern Sweden) reconstructed using biological proxy indicators - Bigler, Christian; Barnekow, Lena; Heinrichs, Markus L.; Hall, Roland I. (Vegetation History and Archaeobotany, 2006)
Holocene environmental and climatic changes are reconstructed using analyses of biological proxies in lake sediments from Vuolep Njakajaure, a lake located near the altitudinal treeline in northern Sweden (68 degrees 20' N, 18 degrees 47' E). We analysed biological proxy indicators from both aquatic and terrestrial ecosystems, including diatoms, pollen and chironomid head capsules, in order to reconstruct regional Holocene climate and the development of the lake and its catchment. During the early Holocene and after 2500 cal B.P., Fragilaria taxa dominated the diatom assemblages, whereas planktonic Cyclotella taxa prevailed during the major part of the Holocene (7800-2300 cal B.P.), indicating the importance of the pelagic habitat for diatom assemblage composition. The planktonic diatoms appeared at the same time as Alnus became established in the catchment, probably altering nutrient availability and catchment stability. The pollen record is dominated by mountain birch (Betula pubescens ssp. tortuosa) pollen throughout the Holocene, but high percentage abundances of Scots pine (Pinus sylvestris) pollen suggest the presence of a mixed pine-birch forest during the mid-Holocene (6800-2300 cal B.P.). Head capsules of Tanytarsini and Psectrocladius dominated the chironomid assemblage composition throughout the Holocene, in combination with Corynocera ambigua after 2300 cal B.P. A quantitative, diatom-based reconstruction of mean July air temperature indicated a relatively cold temperature during the early Holocene (9000-8000 cal B.P.) and after ca. 2300 cal B.P., whereas the mid-Holocene period is characterised by stable and warm temperatures. The overall patterns of Holocene climate and environmental conditions are similarly described by all biological proxy-indicators, suggesting relatively warm conditions during the mid-Holocene (ca. 7800-2300 cal B.P.), with a subsequent colder climate after 2300 cal B.P. However, the onset and magnitude of the inferred changes differ slightly among the proxies, illustrating ...